Analysis of The Impact of Image Messages on Cigarette Packs on Interest to Stop Smoking in Medan City Community - Alya Zuhrah; Bintang Rizki Angeli; Maharani Harahap; Meuthia Ulyna Zahra; Nia Syahfitri Damanik; Uli Syahri Rizki (Pena Cendekia Insani, 2021)
The regulation on graphic warnings on cigarette packs is governed by Minister of Health Regulation No. 28 of 2013 about the Inclusion of Warnings and Health Information on Tobacco Product Packaging. Smokers should also be urged to quit smoking by seeing frightening image messages on their cigarette packets. The goal of this study was to determine the effect of graphic messaging on cigarette packs on the interest of Medan residents in quitting smoking. This study used a quantitative Likert scale and 100 respondents to collect primary data. In this study, data were gathered through the use of a questionnaire and an online Google form. In this study, the data are analyzed using univariate analysis along with descriptive statistics. The results indicated that 64% of respondents smoked daily, 36% smoked occasionally, and 58% started smoking between the ages of 16 and 23. Cigarette picture message number 4 received the highest response value, namely 7-8. While the majority of respondents chose picture number 1 with a score of 5-6 as the image message that increases their intention to quit smoking, To discourage smoking behavior in the society, the government must increase the image message on cigarette packets. To enhance people's intentions to quit smoking, socializing about smoking image messaging should be provided.